Experimental Study and Numerically Supported Approach to Interpretation of Spontaneous Transitions into a State of High Conductivity in Poly(vinyl chloride) Composite Films - Vlasov, D.V.; Kryshtob, V.I.; Apresyan, L.A.; Vlasova, T.V. (Journal of Composites and Biodegradable Polymers, 2014)
The results of experimental studies of conductivity anomalies are analyzed for film samples of specially synthesized PVC and polyacetylene copolymer, in which polyene conjugated bonds are built in PVC macromolecules. In such samples spontaneous and stimulated conductivity jumps by 12 orders of magnitude take place, and the lifetime of each of these states can be very large - minutes, hours and more. The nonlinear model is considered which describes the anomalous behavior of conductivity as a result of percolation transition associated with reversible thermal "shorting" of insulating gaps between conductive regions.